Sustainability of Food Systems: An Analysis of Household Food Waste on the Economy, Society, and Environment in Maryland, USA - Akande, Adekoya Alex; Owolabi, Abayomi Justine (Journal of Sustainability and Environmental Management, 2024)
Sustainability involves actions that consider environmental, social, and economic aspects. Food waste is a major issue, accounting for nearly one-third of the global food supply and resulting in significant environmental, economic, and social consequences. Preventing food waste, especially at the household level, is crucial due to the high levels of wastage. This study investigates the environmental, economic, and social impacts of food waste on the sustainability of family food systems in Prince George's and Montgomery counties, Maryland, USA. Primary data was collected through an online survey and personal interviews, utilizing the IBM SPSS statistical data tool. The methodology evaluation employed a 5-point Likert-type frequency scale, with scores ranging from 'strongly agree' (5) to 'strongly disagree' (1). The study's findings reveal several critical points. Firstly, consumers frequently dispose of leftover food, which adds to the accumulation of waste in landfills. Secondly, the energy and water expended in preparing food that is ultimately discarded pose significant environmental costs for households. Lastly, the issue of food waste not only exacerbates hunger but also contributes to global food insecurity, emphasizing the need for more sustainable food practices and waste management strategies.